المصطلح النقدي عند محمد بنيس في كتابه الشعر العربي الحديث بنياته و ابدالاتها - رضواني, شكيمة, السعيد مفتاح; عروة, عيسى (University of El-oued, 2022)
تكمُن أهمية هذا البحث الموسوم بــ: المصطلحالنقديعندمحمدبنّيسفيكتابه "الشعــرالعـربيالحديث،بنياتهوإبدالاتها"إلى إبراز وتجلية المصطلح النقدي عند "محمد بنيس"، كما أن الغاية المنشودة من وراء هذه الدراسة الوقوف على المصطلحات التي استخدمها في تعبيره عن المصطلح النقدي في ثنايا كتابه، وحتى يتسنى تحقيق تلك الغاية المرجوة اقتضى منا تقسيم هذا البحث إلى مقدمة ومدخل تمهيدي وفصلين وخاتمة إشتملت على أهم النتائج. فأما المقدّمة احتوت على العناصر التالية: تمهيد حول الموضوع، والإشكالية، كما بيّنا فيها المنهج المتبع، والصعوبات التي واجهتنا، وكذلك أشرنا إلى أهم المصادر والمراجع المعتمد عليها. وأما المدخل التمهيدي فقد عرّجنا فيه إلى تعريف المصطلح ونشأته وآليات صياغته، كما أبرزنا كذلك تعريف النقد وأنواع ووظائفه. وأما في الفصل الأول فتطرقنا فيه إلى مفهوم المصطلح النقدي ونشأته ومناهجه ومشكلاته وأهم جهودالباحثينالعربفي الحد منها. وأما في الفصل الثاني فكان الكلام فيه منصبّا على الجانب التطبيقي للدراسة، وقد تضمّن جملة من المصطلحاتالنّقديةالتيأوردهامحمدبنيسفيكتابه:"الشعــرالعــربــيالحديثبنياتهوإبـــدالاتها"، من بينها: التناص، الــبِـــنــويّة، الهيمنة الثقافية، النسق.... كما ذيلنا الدراسة بخاتمة اشتملت على جملة من النتائج وإليك أبرزها:  أعطىبنيسلكلمصطلحنقديمثالوجعلالقارئهوالذييستنبطتعريفهمنخلالالقراءةالفاحصةوالعميقةللمصطلح.  بنيس تأثر بالمصادر العربية القديمة والمصادر الغربية الحديثة فجمع بينهما لتكون دراسته موفقة ومتكاملة بين ما هو تقليدي وما هو حداثي.  بنيس لم يستشهد ويعتمد على آراء سابقين في تحديد معنى ودلالة المصطلح، بل اعتمد على رأيه الخاص من خلال تجربته النقدية.  اعتمد الناقد في مدونته على إعطاء أمثلة وشرح كل مصطلح ومحاولة تبسيطه للقارئ، وهنا تتجلى سلاسة وبساطة الأسلوب. The importance of this research, tagged with: The Critical Terminology of Muhammad Bennis in his book "Modern Arabic Poetry, Its Structures and Its Substitutions" is to highlight and clarify the critical term for “Muhammad Bennis”, and the aim behind this study is to identify the terms he used in his expression of the term. Criticism in the folds of his book, and in order to achieve that desired goal, it required us to divide this research into an introduction, an introductory introduction, two chapters, and a conclusion that included the most important results. As for the introduction, it included the following elements: an introduction to the topic, the problematic, as we explained the approach followed, the difficulties we faced, and we also referred to the most important sources and references relied upon. As for the introductory introduction, we have referred to the definition of the term, its origin and the mechanisms of its formulation, and we have also highlighted the definition of criticism and its types and functions. In the first chapter, we discussed the concept of the critical term, its origins, methods, problems, and the most important efforts of Arab researchers to reduce them. As for the second chapter, the discussion was focused on the practical side of the study, and it included a number of critical terms mentioned by Muhammad Bennis in his book: “Modern Arabic Poetry: Its Structures and Its Changes,” among them: intertextuality, structuring, cultural hegemony, pattern.... We also appended the study with a conclusion that included a number of Results, and here are the most prominent of them:  Bennis gave each critical term an example and made the reader the one who derives its definition through a careful and deep reading of the term.  Bennis was influenced by ancient Arab sources and modern Western sources, so he combined them to make his study successful and integrated between what is traditional and what is modern.  Bennis did not cite and rely on previous opinions to determine the meaning and significance of the term, but rather relied on his own opinion through his critical experience. The critic relied on his blog on giving examples and explaining each term and trying to simplify it for the reader, and here the smoothness and simplicity of the style is evident
Keywords: The critical term, Muhammad Bennis, criticism, poetry.; المصطلح النقدي، محمد بنيّس، نقد، شعر